The effect of a directional split flow ratio on bidirectional pedestrian streams at signalized crosswalks. (18th July 2018) - Zhang, Jun; Wang, Qiao; Hu, Yanghui; Cao, Shuchao; Xia, Long; Song, Weiguo
Abstract: A signalized crosswalk is a time and space constraint facility, the capacity of which is influenced by bidirectional pedestrian movement as well as external effects such as signal timing and geometry. Actual manuals and literature report different descriptions of the capacity of crosswalks. In this paper, pedestrian movement properties on a signalized crosswalk are studied by carrying out a series of experiments under laboratory conditions. The formation of lanes during the movement is analyzed and different patterns are observed from video recordings. Not only does the number of lanes in the bidirectional flow depend on the corridor width, but it also depends on the spatial distribution of the leaders in the stream. The influence of the directional split ratio in bidirectional streams on the capacity of crosswalks and crossing time is investigated. The maximum reduction of the capacity occurs at a directional split ratio of 0.5, which agrees with the findings of Alhajyaseen et al, but is different from the descriptions in the high capacity manual. However, the observed maximum flow is higher than that in previous studies. By comparing the fundamental diagrams of bidirectional flow on crosswalks and in corridors, it is found that the specific flow of bidirectional movements is less influenced by the density for in both scenarios, but the values show certain differences. It indicates that the influence of the directional split flow ratio on the bidirectional pedestrian flow should not be ignored. These findings allow us to understand the differences of uni- and bidirectional flow and are useful to facilitate designs.